Ship-based Trackline Geophysical Data (MGD77) acquired during the Nathaniel B. Palmer expedition NBP0304A (2003) ... - Swift, Jim (Interdisciplinary Earth Data Alliance (IEDA), 2008)
This data set was acquired with a ship-based Gravimeter and Subbottom Profiler, Gravimeter, Navigation system, and L and R Gravimeter during Nathaniel B. Palmer expedition NBP0304A conducted in 2003 (Chief Scientist: Dr. Jim Swift). These data files are of MGD77 format and include Bathymetry, Gravity (Field and Free Air Anomaly) data that were processed during the cruise. Data were acquired as part of the project(s): Western Arctic Shelf-Basin Interaction, and funding was provided by NSF grant(s): OPP01-25399 ...